2003
DOI: 10.1046/j.1365-2524.2003.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Proactive, targeted benefits advice for older people in general practice: a feasibility study

Abstract: The aim of the present project was to assess a welfare benefits and advice screening programme offered in a systematic and inclusive way to all patients aged 80 years and over registered with a single general practice. The setting was an inner-city National Health Service group practice with a total of seven full-time general practitioners (GPs) and a list size of 12 000 patients. A total of 280 patients were identified as aged 80 years and over. Using a combination of telephone calls, surgery attendances and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Most of these needs led to referral back to the general practitioner, raising the question whether they would have come to the attention of primary care professionals in the normal course of service use and clinical enquiry, without the team's intervention. The extent to which financial resources can be mobilised confirms the findings from a smaller, practice‐based study in the same area (Toeg et al . 2003) and underlines the importance of benefits advice for the older population.…”
Section: Discussionsupporting
confidence: 79%
“…Most of these needs led to referral back to the general practitioner, raising the question whether they would have come to the attention of primary care professionals in the normal course of service use and clinical enquiry, without the team's intervention. The extent to which financial resources can be mobilised confirms the findings from a smaller, practice‐based study in the same area (Toeg et al . 2003) and underlines the importance of benefits advice for the older population.…”
Section: Discussionsupporting
confidence: 79%
“…Currently, many of the services are transient (Widdowfield & Rickard, 1996;Abbott & Hobby, 1999) and the efficacy of alternative service provision models has not been researched. Emanuel (2002) demonstrated that a physical base within the primary care team facilitates close and effective working; Toeg et al (2003) highlighted the benefits of combining domiciliary and practice based services. This, coupled with long term funding, appears to be central to the acceptance and success of the service.…”
Section: Discussionmentioning
confidence: 99%
“…This could include adapting Toeg et al's (2003) model of expansion of the GP referral process through use of electronic database lists of their over 80+ population, with efforts made to contact every 80+ years client (inclusive of outreach home visits) and provide referrals to financial counsellors through contact letters signed by GPs and follow-up phone calls. The options of systemic framework of financial counselling review for Older Person should be considered.…”
Section: Resultsmentioning
confidence: 99%
“…The options of systemic framework of financial counselling review for Older Person should be considered. This could include adapting Toeg et al's (2003) model of expansion of the GP referral process through use of electronic database lists of their over 80+ population, with efforts made to contact every 80+ years client (inclusive of outreach home visits) and provide referrals to financial counsellors through contact letters signed by GPs and follow-up phone calls. Given Older Persons contact with GPs is relatively high and more frequent in general, this model would also be proactive in outreaching to Older Persons already visiting GPs.…”
Section: Resultsmentioning
confidence: 99%